A strategy for the training of teachers in the field of technology - Sergio Briceño; Samul Herrera (Corporación Universitaria Minuto de Dios, 2004)
The research project goes towards the construction an validity of an educative   work strategy in technology, with pedagogic and didactic features which characterize and define it. It wants to identify different elements and aspects from the representation of the technological knowledge that contribute in a direct and meaningful way to the generation and consolidation of the professional competences in the future technology teachers.  In the technology program in the education faculty. In the same direction it wants to elaborate a proposal about the values and competences that must be developed with the students.